Visual Interpretation: On the Study of European Architectural Graphics of 17th‑18th Centuries - Arutyunyan, Yulia I. (Actual Problems of Theory and History of Art, 2020)
The article deals with the methods of visual interpretation in the context of the problems of “newart history” for the study of works of European drawing and printed graphics of early Modern times. It aims atthe possibilities of expanding the methodological and source base of art studies through the introduction of interdisciplinary approaches to the material. Modern culture generates the new of historicism of thinking focused on the value of memory — from a personal experience and intragroup constant to a social function and collective phenomenon. Actualization of methods of cultural reconstruction and interpretation of visual practices allows usto consider graphics as works of art and as documents of the era, revealing the scope of aesthetic preferences, customer expectations, ideas of landscape design, concepts of the relationship between architecture and nature. The study has introduced the principles of complex analysis of graphic works, and paid special attention to the ideas of visual rhetoric in the interpretation of images of architecture. The role of the customer’s personality, the question of goal-setting in the creation of graphic cycles, and the features of cartography and travelogues raised the issue of social role and political representation in the selection of visual motifs. A new set of approaches to the analysis of the subject field, the principles of interpretation of the composition, and spatial structures of architectural studies have been suggested, restoration materials and historical reconstructions, scientific and book illustrations, graphic“travel” and species engravings, historical and topographic publications. Methods for visual interpretation of the patterns of realization of architectural forms in a chart help to identify a comprehensive principle of existence of such images in European culture 17th‑18th centuries. Appeal to the images of Gothic creates not only a negative assessment of aesthetic features of the style, but the interpretation of the principles of using of motives for rhetorical indications of the antiquity of the tradition and commitment to the ideals of power and faith.
Keywords: visual studies; visual rhetoric; book illustration; scientific illustration; printed graphics; architectural graphics; topographic engraving; graphic image of architecture; landscape in graphics; panoramic landscape